Economic-statistical design of variable parameters s chart. Issue 5 (2nd September 2020) - Lee, Ming Ha; Khoo, Michael B. C.; Chew, Xinying
ABSTRACT: In this paper, the economic-statistical design of the variable parameters (VP) s chart is investigated, where all the design parameters of the s chart are allowed to vary between two values as a function of the most recent process information. The optimal design parameters of the VP s chart are derived based on the economic and statistical criteria. The economic-statistical design is performed by minimizing the cost function with the imposed in-control and out-of-control statistical constraints. The cost of the economic-statistical design is slightly higher than the economic design due to the imposed statistical constraints. The effect of cost and process parameters on the optimal design parameters, statistical performance and minimum expected cost is examined and discussed. The comparison results indicate that the cost of the VP s chart is lower than the variable sample size and sampling interval (VSS) s chart, the variable sampling interval (VSI) s chart, the variable sample size (VSS) s chart and the standard s chart.